HER2/neu expression in correlation with p53 and Ki-67 immunoreactivity and clinicopathological parameters in breast cancer patients. - Yashar, Genghis; Basheska, Neli; Ivkovski, Ljube; Kraleva, Slavica; Prodanova, Irina; Vasev, Nikola; Kubelka-Sabit, Katerina; Smichkoska, Snezhana; Zografski, George (Blackwell Publishing, 2002)
Introduction: Although the role of HER2/neu status is still unsettled, its determination is valuable in selecting breast carcinoma patients for adequate Herceptin therapy. Aims: The purpose of this study was to evaluate the association among HER2/neu, p53 and Ki-67 immunoreactivity, as well as clinicopathological parameters (tumour size, histopathologic grade, nuclear grade, tumour type. lymph-node status and age) in breast cancer patients. Materials and methods: HER2/neu, p53 and Ki-67 expression was determined in 169 post-operative stage I-III (UICC. 1997) breast cancer patients using the standardized DAKO HercepsTest and by immunoperoxidase technique. respectively. The results were evaluated by performing the standardized scoring system. Discussion and conclusion: HER2/neu expression was positive in 66 patients (37%). There was no association between HER2/neu expression and p53 or Ki-67 immunoreactivity as well as any clinicopathological parameter, while the values of Ki-67 and p53 were strongly interrelated (P < 0.001). Ki-67 was also in significant correlation to tumour size, lymph-node involvement and tumour type (P<0.001), while p53 was only related to patients' age (P <0.01). These results indicate that HER2/neu is an independent prognostic marker in differentiating a subgroup of high-risk breast cancer patients. Additional studies are required to adjust HER2/neu testing results to clinical outcome.
Keywords: breast carcinoma; Her2/neu; Ki-67; p53; immunohistochemistry; prognostic factors